Grade 3 coronary artery perforations in chronic total occlusion‐percutaneous coronary intervention: Mechanisms, locations, and outcomes from the G3CAP Registry. Issue 2 (10th June 2022) - Pavani, Marco; Cerrato, Enrico; Franzè, Alfonso; Colombo, Francesco; Ryan, Nicola; Durante, Alessandro; Bellini, Barbara; Calcagno, Simone; Montorfano, Matteo; Gonzalo, Nieves; Azzalini, Lorenzo; Escaned, Javier; et al.
Abstract: Aim: The impact of Grade III coronary perforations (G3‐CP) in the setting of CTO‐PCI is not well assessed. Methods and Results: We reviewed 7773 CTO‐PCI and 98, 819 non CTO‐PCI performed in 10 European centers: G3 perforation occurred in 87 patients (1.1%) during CTO PCI and 224 patients (0.22%) during non CTO‐PCI ( p < 0.001). G3‐CP involved the CTO segment in 68% of patients and the retrograde channels in 14% of cases. In the CTO PCI group, wire induced G3‐CP (50.5% vs. 32.5%, p = 0.02) occurred predominantly when dedicated CTO tapered and highly penetrative wires were used. Intra‐procedural and in‐hospital death rates were 4.6% vs. 5.8% and 3.6% vs. 7.5% respectively for CTO PCI and non‐CTO PCI groups ( p = NS). At a median follow up of 24 months, the overall mortality and MAE were respectively 7.8% and MAE 19% without difference among groups. Conclusions: We showed similar in‐hospital and long‐term outcomes when G3 perforations occurred during CTO PCI and non CTO‐PCI.